Development--The Need for New Directions - Woods, George D. (World Bank, Washington, DC, 2020)
George D. Woods, President of the World Bank Group, spoke of his appreciation of the splendid support and encouragement the Bank receives from the Swedish community. Sweden’s exemplary support for the International Development Association (IDA) has an importance and a significance beyond the actual capital sums that it has made available. IDA aid helps developing peoples achieve a steady advance toward their goals of modern productivity, appropriate modern education, and self-reliant growth.